Linear prediction based packet loss concealment algorithm for PCM coded speech. - Gunduzhan, E. (IEEE Transactions on speech and audio processing)
One of the well-known problems in real-time packetized voice applications is the degradation in voice quality due to delayed or misrouted packets. When a voice packet does not arrive at the receiver on time, the receiver needs a packet loss concealment algorithm to generate a signal instead of the missing voice segment. In this paper we describe a high performance packet loss concealment algorithm for pulse code modulation (PCM) coded speech. The algorithm extracts the residual signal of the previously received speech by linear prediction analysis, uses periodic replication to generate an approximation for the excitation signal of missing speech, and generates synthesized speech using this excitation. It also performs overlap-and-adding and scaling operations to smooth out transitions at frame boundaries. The new algorithm is compared to other algorithms by subjective quality tests, and is found to be better than the existing algorithms in some cases